Effects of multimorbidity coexistence on the risk of mortality in the older adult population in China - Su, Zhili; Huang, Li; Zhu, Jinghui; Cui, Shichen (Frontiers in Public Health, 2023)
Background: Multimorbidity coexistence is a serious public health issue affecting a significant number of older adults worldwide. However, associations between multimorbidity and mortality is rarely studied in China. We assessed the effects of multimorbidity coexistence on mortality among a nationwide sample of older adults from China. Objective: We analyzed 10-year (2008-2018) longitudinal data of 12,337 individuals who took part in China, a nationwide survey of people 65 years and above. We used the Cox proportional hazard model to determine the effects of multimorbidity on the all-cause mortality risk. We also examined mortality risk between sex and age are obtained through differential analysis. Results: At baseline, 30.2%, 29.9%, and 39.9% of participants had 0, 1, and 2 or more diseases, respectively. The cumulative follow-up of this study was 27,428 person-years (median follow-up was 2.7 years; range, 0.01-11.3 years), with 8297 deaths. The HRs (95% CIs) for all-cause mortality in participants with 1, and 2 or more conditions compared with those with none were 1.04(0.98, 1.10), and 1.12(1.06, 1.18), respectively. Stratified analysis showed that compared with those with no disease and single disease who aged 65-79, participants who were 80-94 years with 2 and more diseases 1.11 (1.01, 1.23) had the highest mortality risk. Gender was associated with mortality, the hazard ratio for males and females in older adults with 2 or multiple diseases is 1.15 (1.06, 1.25) and 1.08 (1.01, 1.17), respectively, compared with those with no disease and single disease. Conclusion: Multimorbidity coexistence is associated with an increase in an increased risk of death in older individuals, the effect is relatively significant in the 80-94 years.